Ethylene-mediated resistance to bacterial canker in kiwifruit is suppressed by cool temperature - Zhiran Wu; Qianqian Dang; Shuni Ouyang; Wei Liu; Lili Huang (Horticultural Plant Journal)
Ambient temperature affects the occurrence and prevalence of plant disease. Most bacterial diseases are damaging at high temperatures. However, kiwifruit bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa) has been found to be prevalent at relatively cool temperatures, and it is unclear how ambient temperature affects the development of kiwifruit bacterial canker. In this study, basal resistance to Psa was suppressed in kiwifruit at cool growth temperature (16 °C) compared with at normal temperature (24 °C). In addition, RNA sequence analysis and ethylene content assessment indicated that ethylene modulated kiwifruit resistance to Psa at normal growth temperature and that cool temperature inhibited ethylene accumulation and Psa-induced activation of the ethylene signaling pathway in kiwifruit. Virus-mediated silencing of the kiwifruit ethylene signaling gene AcEIN2 suppressed kiwifruit resistance to Psa at normal growth temperature. Exogenous application of ethylene inhibitor 1-methylcyclopropene eliminated the difference in kiwifruit resistance to Psa at 16 and 24 °C. Exogenous application of ethylene analogues ethephon induced resistance to Psa in kiwifruit. In conclusion, cool temperatures impair basal resistance to Psa by reducing the activation of ethylene biosynthesis and signaling in kiwifruit. The results provide clues for new strategies to control plant diseases in a context of global environmental change.